Designing and Implementing a Navicat Database System for a Call Center - Hamtini, Thair M.; Rababah, Osama (International Journal of Advanced Corporate Learning (iJAC), 2011)
A call center is a physical place where customer and other telephone calls are handled by an organization, usually with some amount of computer automation. Typically, a call center has the capacity to handle a considerable volume of calls at the same time, to screen calls, forward calls to qualified person to handle them, and to log calls. In this article we proposed an architecture and showed how the system works. Carolina Call Center used to manually keep track of its call information through different programs. Data would be entered on Microsoft Excel and results were displayed on Microsoft Word. This made it hard to keep track of the data in an organized matter. Since many Call Centers may encounter these problems, we found a solution by creating a database. We used Navicat as a database client, and Dreamweaver as a web-interface design. Every agent now had an employee account with a password. Each account gave the agents access to the different campaigns they were working on. The accounts also had a timer as well as a break button that automatically kept track of login, logout and breaks. Not only did the database automate work to the employees, but it was beneficial to be business as well. The decreased number of errors combined with the reduced need for employees helped the call center save money. Since the database is an efficient timesaver, it decreased the number of working hours for both management and employees. The database greatly improved the overall quality of the Carolina Call Center.